Review on relationship between co-operative, credible, conversational, and consistency of sustainable brand as a determinant factor of consumer buying behaviour for cosmetics products - Tan, Chiew Ying; Sidah Idris; Wajiran Sinun (Penerbit Universiti Malaysia Sabah, 2020)
In the globalization era, the improvement of technology, science, society, economy, and education provide people to have a better standard of living and styles and lead to a major emphasis on beauty and physical attractiveness. Cosmetics and skincare are important today because its help to enhance people appearance and make them feel more confidence and assurance of individual to meet the challenges of society than ever before. This study aims to examine the co-operative, credible, conversational, and consistency as a determining factor which influence consumer buying behaviour in cosmetics products manufactured in Malaysia or overseas which marketed within Malaysia. Besides that, this study will only be focusing on Gen Y and Gen Z respondents those staying in Kota Kinabalu, Sabah. Secondary data will be used to identify the relationship between co-operative, credible, conversational, and consistency and consumer buying behaviour of cosmetics products. This study finding expected to determine factors influence consumers buying behaviour towards cosmetics products and contribute to the existing theory of this study. Thus, based on the previous studies shown significant relationship between co-operative, credible, conversational, and consistency and consumer buying behaviour of cosmetics products.